The extent of awareness of the importance of using Mobile Learning systems among students specializing in Educational Technology at Tiaz University in Yemen - Al-Hidabi, Dawood Abdulmalek Yahya; Saleh, Eissa Muhammad Ali; Saif, Hanan Abdu Farhan (University of Science and Technology, Aden, Yemen, 2023)
Abstract The aim of the research is to investigate the extent of awareness regarding the skills of utilizing the Mobile Learning (M-Learning) system among students specializing in Educational Technology at Taiz University. In order to achieve the research objective and address its inquiries, a descriptive-analytical methodology was depending on this methodology is used in the analysis and investigation of research phenomena. The research sample comprised graduate students specializing in Educational Technology enrolled in the master’s program at Taiz University for the academic year 2023/2024, totalling 63 male and female students. A questionnaire was used as the data collection tool. Upon gathering and statistically analysing the research data, the results indicated that the research sample students possess awareness of the importance of mobile learning, with their awareness primarily cantered around the fundamental skills of utilizing mobile learning. The results also demonstrated a moderate level of awareness among students regarding their use of mobile learning skills. Their mobile and smart device use is largely restricted to communication and basic applications. However, there is a significant deficiency in their awareness of using mobile devices to access information online, engage in online courses, attend virtual conferences, and other skills available for students' educational and learning benefit. Several suggestions were put forward by the students to enhance effective utilization of mobile learning skills in education and learning. Among these suggestions were raising awareness about mobile learning skills and organizing training courses to equip students with the ability to employ mobile devices in the educational process. Consequently, a number of recommendations were made, including the necessity of incorporating mobile learning as a curriculum component for students, arranging training and awareness sessions on mobile learning skills, fostering students' interest, and encouraging them to acquire mobile learning skills. Additionally, the importance of being cognizant of the diverse uses of mobile learning to keep up with contemporary developments was emphasized. Keywords: Mobile Learning, Awareness of Mobile Learning Skills, Educational Technology Students.